Implementasi Sensor Akselerometer pada Lengan Manusia untuk Mengendalikan Pergerakan Lengan Robot - Achmad Rizal Zakaria; Wijaya Kurniawan; Dahnial Syauqy (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Robot arm or commonly known as Robot Manipulator is one types of robot that mostly used by the industrial society. Robot arm is generally controlled by a joystick and button. The inventor wanted to design a robot arm control system using sensors accelerometer combined with microcontroller Arduino UNO. Robot manipulator will be controlled by a human hand and arm so that the robot can follow the movements of the hand and arm. Microcontroller hardware implementation is suitable with the design in the microcontroller which uses 2 modules MPU6050 accelerometer sensor, an Arduino Nano, also cable as a medium for data transmission. This microcontroller as the data receiver from the accelerometer sensor 1 and 2 which then being processed and produced by output that will end on the robot manipulator. Test placing of sensor aims to determine the value of each sensor position on the arm and to know the right position to put the accelerometer sensor. In this test the result value can change, when the sensor is placed on the arm at a distance of 10cm from shoulder is 151â°-152â°, 18cm from shoulder 157â°-158â°. This is because the accelerometer sensor mpu6050 has high sensitivity when mounted on a moving object, the sensor values can change quickly even though the object is only moving little bit